Sams teach yourself object oriented programming in 21 days - Sintes, Tony (Sams teach yourself in 21 days., 2002)
Sams Teach Yourself Object Oriented Programming in 21 Days differs from other OOP books in two main ways. Many classic OOP books are designed for software engineers and teach at an academic level. Sams Teach Yourself Object Oriented Programming in 21 Days presents accessible, user-friendly lessons designed with the beginning programmer in mind. Other OOP books work to present both OOP and to teach a programming language (for example: Object-Oriented Programming in C++). Although Sams Teach Yourself Object Oriented Programming in 21 Days uses Java to present the examples, the book is designed to present concepts that apply to any OOP environment.